The Role of Deliberative Democracy in Systemic-Structural Transformation for Sanitation Issues - Sa'at, Meutia Ramadhani; Wibawa, Satriya (Jurnal Paradigma, 2024)
This research explores the complex dimensions of sanitation issues, particularly focusing on the systematic structural transformation needed for long-term and resilient changes in achieving equitable access to clean water and sanitation. Utilizing a qualitative descriptive approach, the study draws insights from the case of West Java, exemplifying challenges arising from geographical conditions, industrial waste exposure, and limited public understanding. Emphasizing the importance of inclusive policies, the research underscores the significance of participatory deliberative democracy, as advocated by Jurgen Habermas, in addressing sanitation complexities. The findings reveal the necessity for a holistic and sustainable approach to sanitation policies, actively involving marginalized communities in decision-making processes. By examining successful grassroots initiatives and adopting a collaborative, affordable, and socially aware model, the study recommends a comprehensive strategy to integrate sanitation improvements into broader poverty alleviation and property security agendas. Ultimately, the research emphasizes the importance of societal collaboration, affordable solutions, and a nuanced understanding of socio-economic issues in addressing sanitation challenges in informal settlements.